Technological Risks (GMO, Gene Editing), What Is the Problem With Europe? A Broader Historical Perspective - Kuntz, Marcel (Frontiers in Bioengineering and Biotechnology, 2020)
Europe is often the center of origin of restrictions regarding biotechnology (e.g. GMOs and more recently gene editing). There have been many comments on the negative consequences for these technologies. The causes have already been analyzed in relation to European regulations, but not to its deep-embedded roots. This is what the present article attempts to do. It first depicts the broader historical background in Europe, the rise of a new ideology aiming to avoid repetition of the tragedies of the past, and the way these postmodern ideas have been transposed to science, with a focus on the issue of technological risk. Europe is also compared to the USA.